(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
As a result of violation of the normal movement mode of vehicles on highways, city streets and squares, people may be killed or injured, as well as damage to vehicles and their loads, damage to artificial structures on the road, or other types of material damage. Accidents that cause accidents are called traffic accidents. According to this tariff, there are typically two factors in an accident, these are: death of people, physical injury or a large amount of material damage, as well as the presence of a vehicle in motion